Clinical Outcome of Cefiderocol for Infections with Carbapenem-Resistant Organisms - Monirul I. Sajib; Melinda Monteforte; Roderick Go (MDPI AG, 2023)
Cefiderocol is a novel cephalosporin recently approved by the FDA to aid clinicians in the fight against multidrug-resistant (including carbapenem-resistant) gram-negative organisms. The primary objective of this study is to evaluate the 14- and 28-day mortality associated with cefiderocol. We performed a retrospective chart review of all adult patients admitted at Stony Brook University Hospital between October 2020 and December 2021 and received cefiderocol for at least 3 days. Patients were excluded if they received more than one course of cefiderocol therapy or remained hospitalized at the time of this study. A total of 22 patients met the inclusion criteria. The all-cause mortality on day 28 for all patients was 13.6%, whereas this rate for patients with BSI was 0%, with cUTI was 0% and with LRTI was 16.7%. The all-cause mortality on day 28 for patients who received the dual antibiotics (in conjunction with cefiderocol) was 0%, compared to 25% for patients who only received cefiderocol (p = 0.25). We noted treatment failure in two patients (9.1%). Our findings suggest that cefiderocol could possibly be associated with lower all-cause mortality than previously thought. In our study, we did not find any significant difference between cefiderocol's use in combination with another antibacterial agent and its use as a monotherapy.